Analisa Partikulat Debu, SO Dan NO2 Pada Industri Manufaktur Di Surabaya - Suwanto, Yudha Eka Putra; Kusuma, Maritha Nilam (Universitas Tanjungpura, 2023)
This study aims to determine how much dust, SO2 and NO2 concentrations are in the air and to know the description of the distribution of air in the study site. In addition, this research also aims to design air pollution control devices that can be used to control the emissions produced. The method in this research uses the Gausse method in modeling and uses AERMOD software and Google Earth to complete the model description. It is known that the farthest distance the highest concentration of dust spread is 0.071 km with a dust concentration of 101.3 µg/m3. The farthest distance the highest concentration of SO2 spread was at a distance of 0.051 km with a value of SO2 concentration of 6753.3 µg/m3. The farthest distance the highest concentration of NO2 spread was at a distance of 0.051 km with a value of NO2 concentration of 91.45 µg/m3. The air controller uses a bag filter with 6 compartments for dust control and uses silica absorbent and activated charcoal for controlling NO2 and the Flue-Gas Desulfurization (FGD) method for SO2.